An educational intervention improved knowledge of dietary supplements in college students - Chiba, Tsuyoshi; Kobayashi, Etsuko; Okura, Takashi; Sekimoto, Masashi; Mizuno, Hideya; Saito, Maki; Umegaki, Keizo (BMC public health, 2020)
We have previously reported on the prevalence of dietary supplements among college students; it was deduced that their intake of supplements increased according to their grade (i.e., 13.1% in the first grade to 20.5% in the sixth grade). We also reported that some students had experienced adverse events in Japan due to their intake of these supplements. However, awareness of dietary supplements among college students remains limited, even among pharmaceutical students. Being appropriately educated about them is important for pharmaceutical students, both for themselves as well as for their future careers as pharmacists. We conducted a lecture-based educational intervention about dietary supplements on 328 college students in Japan-184 from pharmaceutical science and 144 from environmental science or food and life science disciplines. The purpose of this study was to evaluate the effects of an educational intervention on college students' understanding of dietary supplements. The intervention involved a lecture that covered the quality of dietary supplements, how they differed from drugs, and a summary of their adverse events. The lecture was evaluated using a 14-question questionnaire. We then compared the pre- and post-intervention responses to the same questionnaire using a Wilcoxon signed-rank test. The questions were assessed using a Likert scale that ranged from "strongly agree" to "strongly disagree"; the latter being the preferred answer. Before the intervention had taken place, the students' understanding of dietary supplements was shown to be deficient. Conversely, post-intervention, their knowledge levels had significantly improved, especially concerning agreement on whether "Dietary supplements are safe because they are just food items". Pre-intervention, 2.7% strongly agreed and 37.5% agreed; post-intervention, 1.2% strongly agreed and 15.6% agreed. On whether "Dietary supplements made from natural ingredients or herbs are safe", at the pre-intervention stage 2.8% strongly agreed and 44.0% agreed and post-intervention, 2.2% strongly agreed and 16.9% agreed. On whether "Dietary supplements made from food items are safe", 4.0% strongly agreed and 43.6% agreed pre-intervention and 0.9% strongly agreed and 16.6% agreed post-intervention. Despite there being a greater number of pharmaceutical students who had a correct understanding of dietary supplements before the intervention, these students still showed improvement after the lecture. An intervention in the form of a single educational lecture has the capacity to improve college students' understanding of dietary supplements. It is important for pharmacists to be appropriately educated about dietary supplements when they consult with patients. We will evaluate the long-term effects of the intervention on the alumni (pharmacists) in a subsequent study.